Dynamic Changes of DNA Methylation During Wild Strawberry (Fragaria nilgerrensis) Tissue Culture - Cao, Qiang; Feng, Yuxi; Dai, Xiongwei; Huang, Lin; Li, Jiamin; Tao, Pang; Crabbe, M. James C.; Zhang, Ticao; Qiao, Qin (Frontiers in Plant Science, 2021)
Tissue culture is an important tool for asexual propagation and genetic transformation of strawberry plants. In plant tissue culture, variation of DNA methylation is a potential source of phenotypic variation in regenerated plants. However, the genome wide dynamic methylation patterns of strawberry tissue culture remain unclear. In this study, we used whole-genome bisulfite sequencing (WGBS) to study genomic DNA methylation changes of a wild strawberry Fragaria nilgerrensis at six stages: from explants of shoot tips to outplanting and acclimation. Global methylation levels showed that CG sites exhibited the highest methylation level in all stages with an average of 49.5%, followed by CHG (33.2%) and CHH (12.4%). Although CHH accounted for the lowest proportion of total cytosine methylation, it showed the most obvious methylation change and the most of these changes occurred in the transposable element regions. The overall methylation levels alternately decreased and increased during the entire tissue culture process and the distribution of DNA methylation was non-uniform among different genetic regions. Furthermore, much more differentially methylated regions (DMRs) were detected in dedifferentiation and redifferentiation stages and most of them were transposable elements, suggesting these processes involved activating or silencing of amounts of transposons. The functional enrichment of the DMR-related genes indicated that genes involved in hormone metabolic processes, plant development and the stress response changed methylation throughout the tissue culture process. Finally, the quantitative real-time PCR (qRT-PCR) was conducted to examine the association of methylation and gene expression of a set of different methylated genes. Our findings give deeper insight into the epigenetic regulation of gene expression during the plant tissue cultures process, which will be useful in the efficient control of somaclonal variations and in crop improvement.